Lessons Learned as President/CEO Bringing a Company from Obscurity to “Medical Device Company of the Year” - Christie, David B. (CMBES Proceedings, 2010)
The business challenges in the commercialization of medical devices are unique and for early stage Canadian companies may be amongst the most demanding of any industry. Ours is an industry that is faced with some unusual complexities, any of which can spell the demise of an otherwise successful technology. Like any technology, the journey to commercialization begins with a great idea, progresses through development and in to clinical evaluation, which ultimately may realize successful commercialization. Unlike many other technologies, we have numerous hurdles outside of our control, including tough regulatory requirements, mandatory ISO and FDA quality systems, reimbursement by third parties, slow conservative adoption rates by medical practioneers and restricted access to capital by an investment community that often does not understand or appreciate these complex and unique challenges. Nowhere do these challenges manifest themselves more than they do for the President and Chief Executive Officer of an early-stage publicly traded medical device company. Imagine you step in to a company with one medical device product, which had been marketed in one specialized niche for a decade without any substantive product improvements, and was generating only 3 million a year in revenue for the past two years, while generating no operating profit. Now imagine what it takes to more than double revenues in the next two years and generate almost 1 million in operating profits. While you are at, completely re-invent the core product, secure numerous complimentary products and enter numerous new markets. Do this without raising any new equity to finance these initiatives and keep your shareholders and Board on-side. These are the challenges of commercialization that take some of the best engineered products in the world and get them across the chasm in to mainstream markets or not. This is one such story from real-live first-hand experience.